What corpus data reveal about the Position of Antecedent Strategy: anaphora resolution in Spanish monolinguals and L1 English-L2 Spanish bilinguals - Lozano, Cristóbal; Quesada, Teresa (Frontiers in Psychology, 2023)
This study investigates the acquisition of anaphora resolution (AR) in Spanish as a second language (L2). According to the Position of Antecedent Strategy (PAS), in native Spanish null pronominal subjects are biased toward subject antecedents, whereas overt pronominal subjects show a “flexible” bias (typically toward non-subject but also toward subject antecedents). The PAS has been extensively investigated in experimental studies, though little is known about real production. We show how naturalistic production (corpus methods) can uncover crucial factors in the PAS that have not been explored in the experimental literature. We analyzed written samples from the CEDEL2 corpus: L1 English-L2 Spanish adult late-bilingual learners (intermediate, lower-advanced and upper-advanced proficiency levels) and a control group of adult Spanish monolinguals (N = 75 texts). Anaphors were manually annotated via a fine-grained, linguistically-motivated tagset in UAM Corpus Tool. Against traditional assumptions, our results reveal that (i) the PAS is not a privileged mechanism for resolving anaphora; (ii) it is more complex than assumed (in terms of the division of labor of anaphoric forms, their antecedents and the syntactic configuration in which they appear); (iii) the much-debated “flexible” bias of overt pronouns is apparent since they are hardly produced and are replaced by repeated NPs, which show a clear non-subject antecedent bias; (iv) at the syntax-discourse interface, the PAS is constrained by information structure in more complex ways than assumed: null pronouns mark topic continuity, whereas overtly realized referential expressions (overt REs: overt pronouns and NPs) mark topic shift. Learners show more difficulties with topic continuity (where they redundantly use overt pronouns) than with topic shift (where they normally disambiguate by using overtly realized REs), thus being more redundant than ambiguous, in line with the Pragmatic Principles Violation Hypothesis (PPVH) (Lozano, 2016). We finally argue that the insights from corpora should be implemented into experiments. The triangulation of corpus and experimental methods in bilingualism ultimately provides a clearer understanding of the phenomenon under investigation.